Specific Detection of Bovine Coronavirus N Protein with TaqMan Probe qRT-PCR - Geng, Jin-Jing; Gong, Zhuan-di; Li, Qyong-yi; Shen, Xiao-yun; Wei, Suo-cheng (Acta Scientiae Veterinariae, 2019)
Background: Bovine Coronavirus (BCoV) can cause acute diarrhea in newborn calves and adult cattle. BCoV infection may cause losses to production by reduced weight gain, reduced milk yield. Several methods have been applied to detect and diagnose BCoV. However, each assay has its deficiency. Currently, real-time quantitative PCR (qRT-PCR) has been utilized to identify and quantify many viral pathogens since it is a highly sensitive. However, the technical assay varies due to normalization control of the signal with an internal standard, typically a housekeeping gene. The main objective of the present study to establish a novel TaqMan probe real-time PCR (qRT-PCR) for detecting BCoV. Materials, Methods & Results: The present study was aimed to establish a novel TaqMan probe real-time PCR (qRT-PCR) for detecting bovine coronaviruses (BCoV), and also to develop a diagnostic protocol which simplifies sample collection and processing. One pair of specific primers, one pair of universal primers and a TaqMan probe were designed from the known sequences of conserved nucleocapsid (N) protein of BCoV. Reaction systems of TaqMan qRT-PCR were optimized including concentrations of the primers and probe as well as annealing temperatures. Prior to optimizing the assay, the recombinant plasmids of pMD18-T-BCoV-N were successfully constructed to make standard curves. The sensitivity, specificity and reproducibility were evaluated on the TaqMan qRT-PCR, respectively. A total of 321 feces specimens collected from diarrheic calves were detected with this assay. The results showed the optimized reaction conditions for qRT-PCR were 14.5 μM/L primers, 19.5 μM/L probes and 45.0°C annealing temperatures. The established TaqMan qRT-PCR assay could specially detect BCoV without detecting any other viruses. Its minimum detection limit was 4.72 × 101 copies/μL. However, universal PCR could detect only 4.72 × 103 copies/μL. Its sensitivity was 100-fold stronger than universal PCR. In conclusion, this TaqMan qRT-PCR had excellent specificity, sensitivity and stability with a 100-fold sensitivity stronger than universal PCR. Minimum detection limit was 4.72 × 101 copies/μL. This method was a cost-effective method to diagnose diarrhea and distinguish pathogens in dairy farms. Discussion: In this study, the authors developed a quantitative real-time PCR (qRT-PCR) in this study based on the TaqMan probe of BCoV. This TaqMan qRT-PCR assay selected and used one pair of specific primers (BCoV-qF/BCoV-qR) and a specific TaqMan probe (BCoV-probe) targeting the conserved nucleocapsid (N) gene. The specificity of primers and probes was validated with Primer-BLAST. The specificity of the qRT-PCR was confirmed by the negative control and other six viruses. The findings demonstrated that TaqMan qRT-PCR could only detect BCoV. This verified the qRT-PCR had an excellent specificity. It is obvious that this TaqMan qRT-PCR assay can detect only BCoV with stronger sensitivity and reproducibility than other real-time PCR methods. The sensitivity test indicated the minimum detection limit of the TaqMan qRT-PCR was 4.72 × 101copies/μL, or 47.2 copies/μL. Sensitivity of the TaqMan qRT-PCR assay was increased by 100-fold as compared to universal PCR with a good inter-assay and intra-assay reproducibility. Thereby, based on the high sensitivity of the assay of this qRT-PCR assay it may be a cost-effective method to diagnose BCoV infections and indentify the etiologic agents of diarrhea syndrome in the dairy farms.